The Effect of Implementing a PBL Model Assisted by Rabbit Population Dynamics Media on Ecosystem Material on Student Scientific Attitudes - Sukma Jaya Asmara; Purwati Kuswarini Suprapto; Dani Ramdani (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kuningan, 2026)
This study aims to analyze the influence of the Problem-Based Learning (PBL) model, assisted by the Rabbit Dynamics Population media, on students' scientific attitudes towards ecosystem materials. This study uses a quantitative approach with a quasi-experimental design (posttest-only control group design) involving three groups, namely the experimental class (PBL assisted by simulation media), the positive control class (PBL without media), and the negative control class (discovery learning). The research sample comprised 90 students from class X at SMA Negeri 1 Jatiwaras, selected through purposive sampling. The research instrument was a 23-item scientific attitude questionnaire using a Likert scale that met validity and reliability criteria (α > 0.80). Data analysis was carried out using normality and homogeneity tests, followed by one-way ANOVA, with post hoc tests. The results showed a significant difference in students' scientific attitudes between groups (Sig. < 0.05), with the experimental class having the highest average compared to the positive and negative control classes. Further tests showed that the experimental classes differed significantly from the two control classes, while there was no significant difference between the positive and negative control classes. The increase in scientific attitudes in the experimental class is evident in the indicators of critical thinking, creativity, cooperation, and perseverance. These findings show that integrating the PBL model with the Rabbit Dynamics Population simulation media effectively improves students' scientific attitudes, and it is therefore recommended as a biology learning innovation to support 21st-century skill development.